Borderline Personality Disorder Symptoms and Emotional Functioning: Profiles of Emotion Regulation and Alexithymia - Whyte, Jessica (Curtin University, 2024)
This thesis comprises two studies that explore two aspects of emotional functioning, using the process model of emotion regulation as a conceptual framework. The first study examines the relationship between BPD symptoms and emotion regulation strategies, and the second study focuses on the relationship between BPD symptoms and alexithymia. Our findings highlight that there are distinct patterns of emotional processing that appear to characterise those with high BPD symptoms.